'If you worked well, we wouldn't be in this situation': evoking and managing the context of post-socialism in everyday Bulgarian discourse. Issue 1 (2nd January 2022) - Sotirova, Nadezhda
ABSTRACT: Through a combination of ethnography of communication and contextualization cues, this study examines public discourse (natural observations and interviews) in Bulgaria and illustrates how participants interactionally construct a cultural notion of the 'others' in order to make sense of the country's problematic situation (corruption). The data was examined for the use of contextualization cues and communication symbols, which the participants creatively used to position themselves and others in relation to a corrupt 'other.' The study shows how the participants utilize both local (micro) contextualization cues as well as larger (macro) historical symbols and their meanings in order to frame both their interactional moves and create a political stance for themselves within the country's post-communist present.